2013
DOI: 10.1088/1741-2560/10/3/036014
|View full text |Cite
|
Sign up to set email alerts
|

Single trial analysis of slow cortical potentials: a study on anticipation related potentials

Abstract: Objective. Abundant literature suggests the use of slow cortical potentials (SCPs) in a wide spectrum of basic and applied neuroscience areas. Due to their low signal to noise ratio, these potentials are often studied using grand-average analysis, which conceals trial-to-trial information. Moreover, most of the single trial analysis methods in the literature are based on classical electroencephalogram (EEG) features ([1-30] Hz) and are likely to be unsuitable for SCPs that have different signal properties (suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 71 publications
(120 reference statements)
3
70
0
1
Order By: Relevance
“…On the other hand, as mentioned earlier, the shape of the designed reference signal plays an important role in the performance of cICA. Therefore, investigation of the effect of other types of reference signals such as the common rectangular pulse, smoothed MRCPs (Garipelli et al, 2013), and discriminative-based reference signal (Lee et al, 2016) will be done in the future in attempt to improve detection performance.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, as mentioned earlier, the shape of the designed reference signal plays an important role in the performance of cICA. Therefore, investigation of the effect of other types of reference signals such as the common rectangular pulse, smoothed MRCPs (Garipelli et al, 2013), and discriminative-based reference signal (Lee et al, 2016) will be done in the future in attempt to improve detection performance.…”
Section: Discussionmentioning
confidence: 99%
“…Such a level of decoding requires proper pre-processing techniques (Garipelli et al, 2013) to enhance the SNR of SCPs through the use of spectral and spatial filters. This finding is consistent with previous works on detection of movement intention (Lew et al, 2012a) and movement execution (Niazi et al, 2012; Robinson et al, 2013; Xu et al, 2014), which showed the advantage of low frequency EEG components.…”
Section: Discussionmentioning
confidence: 99%
“…For signals below 7 Hz, we directly used time domain features (EEG amplitude). In particular, for the SCP, Garipelli et al (2013) have compared various spatial and spectral filtering methods to enhance the signal to noise ratio (SNR) of the slow potentials. Their results have shown higher separability index with the use of narrow pass-band filters between [0.1–1] Hz.…”
Section: Methodsmentioning
confidence: 99%
“…MRCPs are quite versatile, since their amplitudes and time courses vary depending on the subject’s psychological status as well as characteristics of the movement being performed such as distance, speed, precision, etc. [8], [9]. Traditionally, MRCPs have been studied by averaging over a large number of trials, since there was high trial-to-trial variability resulting from background neural activity and non-neural artifacts.…”
Section: Introductionmentioning
confidence: 99%